"It's Nice to Have a Little Bit of Home, Even if It's Just on Your Plate" – Perceived Barriers for Latinos Accessing Food Pantries. Issue 4 (3rd July 2020) - Wright, Kathrine E.; Lucero, Julie; Crosbie, Eric
ABSTRACT: The study objective was to identify the barriers for Latinos accessing food pantries from the pantry volunteer perspective. Interviews were conducted with eight food pantry volunteers in Washoe County, Nevada, coded and thematically analyzed using NVivo. The perceived barriers preventing Latinos from accessing food pantries identified included pantry-level barriers (e.g., volunteers' perceptions of client backgrounds) and built environment and societal barriers (e.g., legal, transportation). Recognizing these barriers can help identify intervention targets to build food systems that are culturally inclusive promoting health and well-being for food pantry clients.